2016
DOI: 10.3892/etm.2016.3504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the κ-opioid receptor on the inhibition of 100 Hz electroacupuncture on cocaine-induced conditioned place preference

Abstract: The administration of 100 Hz electroacupuncture has been demonstrated to suppress cocaine-induced conditioned place preference (CPP) in rats, and there is evidence that the κ-opioid receptor may have a role in cocaine addiction. The present study sought to explore the mechanisms underlying the inhibitory effects of 100 Hz electroacupuncture on cocaine-induced CPP in rats. A rat model of cocaine-induced CPP was used in the present study to investigate the following: i) Naloxone treatment (5 and 10 mg/kg) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“… Kong et al.’s (2002 ) study demonstrated that EA caused fMRI signal increases in some brain regions, such as the insula. Additionally, 100 Hz EA at ST36 and SP6 has been shown to suppress cocaine-induced conditioned place preference via KOR in the nucleus accumbens ( Hou 2016 ). In our experiment, we applied 100 Hz EA at the bilateral ST36 and SP6 for 30 min on days 11–12 to observe the effect of EA on pain-related aversive behavior memory behaviors.…”
Section: Discussionmentioning
confidence: 99%
“… Kong et al.’s (2002 ) study demonstrated that EA caused fMRI signal increases in some brain regions, such as the insula. Additionally, 100 Hz EA at ST36 and SP6 has been shown to suppress cocaine-induced conditioned place preference via KOR in the nucleus accumbens ( Hou 2016 ). In our experiment, we applied 100 Hz EA at the bilateral ST36 and SP6 for 30 min on days 11–12 to observe the effect of EA on pain-related aversive behavior memory behaviors.…”
Section: Discussionmentioning
confidence: 99%